Facilitating a 'virtual space' for social change during the COVID-19 pandemic: working with high-risk population using an arts-informed method. Issue 1 (15th March 2022) - Polat, Zehra Melike
Abstract : As participatory methods place an emphasis on 'collaborative research practices … to produce knowledge in collaboration, ' a transition to virtual platforms created challenges in effectively facilitating these collaborations. Because participatory approaches to digital methods are still growing, there is limited information on best practices for working remotely with 'vulnerable' individuals from refugee backgrounds using participatory methods. Given the unexpected requirement to transition to remote research practices as a result of the pandemic, in this article I reflect on my experiences navigating my university's institutional ethics process, transitioning my participatory visual research project with Turkish and Kurdish asylum seekers to a virtual platform, and the challenges that I have encountered in facilitating digital focus groups.